Why can’t our wall paintings last forever? The creation of identity symbols of street art - Alves, Alice Nogueira (SAUC - Street Art and Urban Creativity (repository), 2017)
The concept of ephemerality has been used in the last decades as the opposite of memory preservation. In this article, I seek to understand the valorization of street art as cultural heritage, as well as the strategies that have been adopted for its preservation in a non-institutional context.